Promoting clean energy adoption for enhanced food security in Africa - Li, Ning; Agene, Deborah; Gu, Lihan; Osabohien, Romanus; Jaaffar, Amar Hisham (Frontiers in Sustainable Food Systems, 2024)
The research investigated the idea of clean energy and how it affects food security utilizing panel data from selected African nations. The World Development Indicators (WDI) for the years 2005 to 2022, the Food and Agricultural Organization (FAO), and the Country Policy and Institutional Assessment (CPIA) were the sources of data. The study engaged the generalized method of moments (GMM), and the results showed that clean energy indicators have both beneficial and adverse effects on food security. This is crucial for policy toward the actualization of sustainable development goals of no poverty (SDG1), no hunger (SDG2), clean and affordable energy (SDG7), sustainable cities (SDG11), and climate action (SDG13). The findings of this study will benefit policymakers, governments, and organizations working toward promoting clean energy, sustainable agriculture, and food security in Africa. It will also benefit farmers and communities who rely on agriculture for their livelihoods. By implementing the recommendations of the study, these stakeholders can work toward a more sustainable and secure future for Africa. Additionally, the environment and global efforts to mitigate climate change will also benefit from the reduction in greenhouse gas emissions.